INFLUENCE OF WATER STRESS AND PLANT AGE ON THE YIELD AND CHEMICAL COMPOSITION OF ESSENTIAL OIL FROM Cymbopogon winterianus Jowitt - Muhammad Yusuf Abduh; Izni Nur Ibarahim; Ulya Atika; Robert Manurung; Dedi Suheryadi (BIOTROPIA, 2020)
Citronella oil, which is also known as Java citronella oil, is typically obtained from the leaves of Cymbopogon winterianus Jowitt and has been widely used as an antiseptic, fragrance, flavor, and many other applications. However, systematic studies on the factors affecting the yield and composition of citronella oil are limited. Hence, this study was carried out to investigate the influence of water stress (low to high) and plant age (0.5 to 5 years) on the yield and composition of citronella oil. Citronella leaves were dried at room temperature (26–30 °C) with a relative humidity of 62–74% for 3 days before the citronella oil was extracted using a steam distillation unit. Introducing a high water stress condition to the plants increased the yield from 0.80% (control) to 1.4% (high water stress) dry weight. The geraniol content slightly increased from 15% to 17%, whereas the citronellal content considerably increased from 31% to 44% when the plants were subjected to high water stress in comparison to the control. The oil yield increased with plant age before it reached its plateau at 3.5% dry weight at age 4 years. However, the composition of citronella oil did not significantly vary with plant age.